Growth mechanism of garnet megaporphyroblasts of the Passos Nappe, Southern Brasília Orogen, Brazil - Hartung, Rafael F. [UNESP]; Simões, Luiz S.A. [UNESP]; Trouw, Rudolph A.J.; Silva, Alex J.C.A. (Elsevier, 2020)
The Passos Nappe is an important tectonic unit of the Southern Brasília Orogen with inverted metamorphism, grading from greenschist facies at the base to granulite facies in the upper part. In the central part, of amphibolite facies, mica schist layers contain garnet megaporphyroblasts (3–9 cm diameter) that contrast with the common-size garnet (0.2–1.5 cm diameter) present in other mica schist layers above and below. This paper intends to describe this textural feature in detail and to discuss its genesis. The megaporphyroblasts are ellipsoidal, with major axis parallel to the mineral and stretching lineation, associated with the main foliation (S2). Inclusion trails analysis in forty-six megaporphyroblasts, demonstrate straight internal foliation (Si = S1) in the core, progressively crenulated towards the rim by D2. Si is discontinuous with the external foliation (Se = S2), which wraps around the megaporphyroblasts, indicating early syn-D2 growth. The angle between the axial planes of the included crenulations and S2 in the matrix indicates that the D2 deformation continued after porphyroblast growth. Asymmetric deformation shadows reveal non-coaxial D2 deformation, associated with the emplacement of the nappe (top-to-the SE). The megaporphyroblasts are almandine-rich (73–82%) and spessartine-poor (0.1–2.5%) exhibiting prograde growth zonation. The common-size garnet porphyroblasts of the adjacent micaschists show similar inclusion patterns and chemical zonation indicating a similar tectonometamorphic evolution. A possible origin of the megaporphyroblasts by introduction of fluids along shear zones is discarded because the megaporphyroblasts are distributed along S0//S1 planes that make an angle with S2. Since the porphyroblasts grew early syn-D2, these shear zones should be parallel to S2 which does not match the observations. The chemical data indicate that megaporphyroblast formation is related to a high-Al protolith composition, associated with scarce nucleation sites.
Keywords: Brasília orogen; Garnet megaporphyroblasts; Microtectonics; Passos nappe; Zoned garnet